Performance of a heat exchanger with compound inclined circular-rings and twisted tapes - M. Pimsarn; P. Samruaisin; C. Thianpong; K. Ruengpayungsak; P. Eiamsa-ard; S. Chamoli; S. Eiamsa-ard (My University, 2022)
Optimization was done of the aerothermal performance factor (η) of a tube into which a combination of inclined circular-rings (ICRs) and twisted-tapes (TTs) were installed. The key contribution of this research is determination of the appropriate ICR and TT sizes to produce the best heat exchanger performance. An ICR's purpose is to produce counter-rotating vortices, whereas the TT's role is to create swirl flow within a tube to improve turbulence and transfer cold fluid from the core region to the heated-wall zone. The influence of circular-ring inclination angle (α = 30o, 45o, 60o and 90o), number of twisted tapes (H = 2, 4, and 6) and twist ratios (TR = 1.0, 2.0, and 3.0) on heat transfer and pressure losses were assessed to determine an optimum η condition. The heat transfer and friction factor tend to increase with H values and decreasing TR. The heat transfer of ICRs together with TTs is higher than in a plain tube by up to 128.7% and 155.3%, respectively, while it is better than the transverse circular-ring (α = 90o) and twisted-tape by up to 116.9% and 146.5%, respectively. Furthermore, due to moderate heat transfer and low pressure losses, a maximal η of 1.66 was achieved for α = 30o, H = 2 and TR = 3.0 within the examined range.
Keywords: Heat transfer enhancement; Heat Transfer Mechanisms